Transformasi Bentuk Pertunjukan Ronggeng Pasaman Grup Ganto Saroha Kecamatan Duo Koto Kabupaten Pasaman - Kurniawan Fernando; Martarosa M.Sn; Rafilosa M.Sn (UNIVERSITAS INDO GLOBAL MANDIRI, 2021)
This study aims to determine the transformation of the Ronggeng Pasaman performance of the Ganto Saroha group in Duo Koto District, Pasaman Regency. Ronggeng Pasaman is a performance art consisting of pantun, joget, and music, especially in Simpang Tonang, Pasaman, West Sumatra. The form of the Ronggeng Pasaman show is combining bouncing skills while dancing to the accompaniment of violin and drum music. The show starts at night, and ends until early morning. Currently Ronggeng Pasaman has undergone a transformation, people, especially young people, are less interested and begin to leave their regional arts, so the Ronggeng Pasaman show is rarely displayed. There was anxiety from the artists themselves, then initiatives emerged to attract the attention of the people. So it formed the Ronggeng Pasaman Ganto Saroha group, with the addition of keyboard music instruments in the show. Unlike the Pasaman Ronggeng Performance in general, the Ganto Saroha group does not show male singers with female appearance, but rather singers are real women or men. This study uses qualitative methods, is analytic description, observant participants. The results showed that the transformation carried out by the artists, made the Ronggeng Pasaman performance of the Ganto Saroha group well received and in great demand by all people in Pasaman, and was fully supported by the local government.